Self-Regulated Learning from Texts (ARATEX-R) Assessment Scale (European Journal of Education and Psychology, 2018)
The different models of self-regulated learning suggest that it develops in three phases (think before, think for, think later), and applied to different areas (cognitive, motivational, emotional, behavioral). The aim of this study was to analyze the structural validity of a new assessment tool of self-regulated learning (Assessment Inventory of Self-Regulated Learning from Texts ?ARATEX), developed based on this theory. The results from confirmatory factor analysis supported a smaller version of that scale, with a hierarchical factor structure organized by areas or dimensions (cognition, motivation, planning, evaluation, environmental management) rather than in stages (before, during, after), and a general factor of self-regulation as the only factor second level. The results are discussed with reference to the theory proposed by Paul Pintrich.